TikTok and Indonesian Housewives - Aji P Wibawa; Mokhamad Iqbal; Oktarian Karyanto; Wiliaguna, Prezza; Rifki Fajar; Vishnu Adisaka (Association for Scientific Computing Electrical and Engineering, 2022)
The “TikTok” app, a short music-powered social video platform app. Whether it's dance music, freestyle, or performance. Expressive video-makers to be as creative as possible and imagine freely and express their expressions as funny as possible. Since 2017, the short video industry has been on the rise. The “Tik Tok” application is a music creative short video social software launched in September 2016. In 2017, this application has become the dark horse of many short video applications. The purpose of this study is to determine how the influence of TikTok on housewives. Every individual has a different level of need in using the media. This literature review starts with the use of TikTok social media to its effect on housewives. To meet the objectives of this study, deep interviews were used to collect data from informants.